INVESTIGATING THE RELATIONSHIP BETWEENCARDIOVASCULAR DISEASES AND PHYSICAL ACTIVITY AMONG THE ELDERLY IN YASUJ - Shahamat, M.; Motlagh, A. H.; Alamdari, A. (University of Eloued جامعة الوادي, 2018)
The purpose of this study was to investigate the relationship between cardiovascular diseases and physical activity among the elderly in Yasuj city. The purpose of this research is applied research. It is also subject to analytical research in terms of its nature and method, and it is temporally cross-sectional because it has been done within a certain time. The data were collected from library and field studies in this research. The statistical population of this study was among the elderly referring to the health centers during the period from June to June in Yasuj during the year 2017, of which 745 were the sample size of the study is 255 people by Morgan table. Sampling method was simple random. In this research, a questionnaire was used to analyze the data using Mann Whitney and Chi-Square tests using spss software. The results showed that 34.3% of the elderly had cardiovascular diseases and 48.8% had high blood pressure. Also, 17.1% had a history of at least one stroke. The results show that people who have smoked in middle age are significantly more likely to have cardiovascular disease in their elderly years. On the other hand, Chi-Square test showed a significant difference in the prevalence of cardiovascular disease among people with high blood pressure and those who did not have high blood pressure (P <0.001). The findings also showed that there was a significant difference between the education level and cardiovascular disease (P = 0.001), so that the level of education was inversely related to cardiovascular disease. The results also showed that there was a significant relationship between the rate Walking, exercise, cycling, and midwifery in middle age with cardiovascular disease are significantly different in the elderly.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Elderly; Cardiovascular disease; Physical activity